Adaptation of Wayang Mahabharata characters and stories to Islamic dakwah - Abdul Malik, Hatta (Faculty of Dakwah and Communication, Walisongo State Islamic University, 2024)
Purpose - This research aims to find out what adaptations in the characters and stories of the Mahabharata wayang towards Islamic da’wah which have unwittingly become the culture of all Indonesian people and not just followers of IslamMethod - The research approach is through a historical approach, namely an approach to investigate, understand, and critically explain the past, considering quite carefully the validity of historical sources and the interpretation of historical information sources.Result - This research shows that there are two forms of adaptation, namely first, character adaptation from the meaning of the five Pandawa characters, namely Yudhistira, Bima, Arjuna, Nakula, and Sadewa, to the addition of characters with unique characters called Punakawan with Semar, Gareng, Petruk, and Bagong. Second, changing the storyline regarding changing several stories that are contrary to dakwah Islam, namely polyandry, women resembling men, the arrangement of gods, and the addition of stories that do not yet exist.Implication - The implications of this research can provide insight into the adaptation of the Mahabarata wayang story in Islamic da'wah.Originality/Value - The adaptation of Wayang Mahabharata characters and stories to Islamic da'wah illustrates a creative synthesis between Javanese cultural heritage and Islamic teachings, enabling the transmission of religious values through familiar narrative forms. This cultural integration not only preserves traditional art forms but also makes Islamic principles more accessible and relatable to the local population.